Multimode extraction from dielectric loaded waveguides via method of moments - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2017)
Multimodal interactions for inhomogeneously loaded rectangular waveguide are examined. Method of Moments (MoM) is utilized to obtain the scattered field data. Validation of the approach is performed by comparison with mode matching technique. © 2017 Euraap.
Keywords: generalized scattering matrix; method of moments; rectangular waveguide